2015
DOI: 10.1111/jsbm.12177
|View full text |Cite
|
Sign up to set email alerts
|

Political Empowerment, Rule of Law, and Women's Entry into Entrepreneurship

Abstract: Women's political leadership may contribute to women's entrepreneurship by removing existing constraints on the economic behavior of women, assuming these changes are then enforced. We examine the association of women's political power and a country's rule of law with women's entrepreneurial entry, using the Global Entrepreneurship Monitor dataset combined with other indicators. Both variables are positively associated with women's entry into entrepreneurship, and the association between political empowerment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 73 publications
(97 reference statements)
4
85
0
Order By: Relevance
“…9 See for instance Aldrich and Fiol (1994), Braunerhjelm et al (2015), Busenitz et al (2000), Calcagno andSobel (2014), De Clercq et al (2010), Meek et al (2010), Manolova et al (2008), Spencer and Gomez (2004), Stenholm et al (2013), Valdez and Richardson (2013). related with access to stock markets (Bruton et al 2009), the financial system (Autio and Fu 2015; , hiring and firing rules and controls (Goltz et al 2015;van Stel et al 2007), political structure (specifically corruption) (Chowdhury et al 2015a,b, Estrin et al 2013a, democracy (Bruno et al 2013), and government size and capability (De Clercq and Dakhli 2009;Estrin et al 2013aEstrin et al , 2013b. Finally, we found that including measures of property rights is less common in the literature (Chowdhury et al 2015b).…”
Section: Entrepreneurship and Its Institutional Determinantsmentioning
confidence: 99%
“…9 See for instance Aldrich and Fiol (1994), Braunerhjelm et al (2015), Busenitz et al (2000), Calcagno andSobel (2014), De Clercq et al (2010), Meek et al (2010), Manolova et al (2008), Spencer and Gomez (2004), Stenholm et al (2013), Valdez and Richardson (2013). related with access to stock markets (Bruton et al 2009), the financial system (Autio and Fu 2015; , hiring and firing rules and controls (Goltz et al 2015;van Stel et al 2007), political structure (specifically corruption) (Chowdhury et al 2015a,b, Estrin et al 2013a, democracy (Bruno et al 2013), and government size and capability (De Clercq and Dakhli 2009;Estrin et al 2013aEstrin et al , 2013b. Finally, we found that including measures of property rights is less common in the literature (Chowdhury et al 2015b).…”
Section: Entrepreneurship and Its Institutional Determinantsmentioning
confidence: 99%
“…Rule of law in a country indicates the degree to which rules and regulations are implemented, and it is widely used as a measure of the quality of governance (Estrin & Mickiewicz, 2011;Estrin et al, 2016;Levie & Autio, 2011). In countries where rule of law is weak, corrupt and unfair practices increase transaction costs (Estrin & Mickiewicz, 2011;Sahasranamam & Raman, 2018) and hinder entrepreneurial activity (Goltz, Buche, & Pathak, 2015). However, in countries where rule of law is strongly established, the risk levels for investments decline significantly, resulting in the creation of many new ventures in those countries (Levie & Autio, 2011).…”
Section: Individual Capital Political System and Social Entrepreneurmentioning
confidence: 99%
“…Prior empirical research on the link between institutions and female entrepreneurship reports mixed results (Yousafzai et al, 2015;Goltz et al, 2015;Lee and Marvel, 2014;Thébaud, 2015). Given these inconsistent results, we can suggest that some complexity may persist in the relationship between institutions and women's entrepreneurial behaviors; thus, we emphasize the need to investigate the potential sequential process by which institutions may energize or damage female entrepreneurs' long-term survival and business growth.…”
Section: 3mentioning
confidence: 99%